A preliminary vegetation survey of the Alberta oil sands environmental research program study area ... - Stringer, P. W. (University of Alberta Library, 1976)
Limited time and access constraints restricted this preliminary vegetation survey to Townships 85-103, Ranges 6-12, west of the 4th meridian. This area centres on sites of maximum development north of Fort McMurray (i .e. the GCOS and Sync rude leases). Eighty-four stands were chosen as representative of all the major vegetation types in the study area. These stands were all sampled between August 18 and September 3, 1975. The structure and species composition of each stand was described by assigning each understory species a cover abundance value, measuring strata heights, and by obtaining quantitative data on the tree stratum where appropriate. The stands were classified by means of a cluster analysis method which grouped closely related stands on the basis of overall species similarity. The ten distinct vegetation types defined by cluster analysis are: (i) Fen (ii) Sandbar Willow Scrub (iii) Tall River Alder-Willow Scrub (iv) Tall Willow Scrub (v) Bottomland Balsam Poplar Forest (vi) Upland White ...